PERANCANGAN USER INTERFACE WEBSITE MENGGUNAKAN KANSEI ENGINEERING DI SMK LPS 1 CIAMIS - Ade Kusdiana; Dwicahya Supriatman, Rian; Yudi Permana, Nana (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Website is a digital-based information, which is used for e-commerce, news, school information, and other related functions. For schools, a website is highly beneficial for providing information about the institution, new student admissions, examinations and the most important is serving as a publication medium for new student enrollment. This study aimed to design User Interface (UI) of the SMK LPS 1 Ciamis website focusing on design landing page as a medium for school publication during the new academic year.The research method employed Kansei Engineering, a methodology that link users’ emotions and experiences with design elements. In this research, the process was carried out through direct fieldwork to collect data, conduct interviews, and gather questionnaire responses. Interviews and questionnaires were utilized to assess the emotional responses of respondents in the process of designing the website’s User Interface (UI). The findings of the User Interface website design research which employed the Kansei Engineering method at SMK LPS 1 Ciamis, were derived from interview data, the identification of Kansei words, and the collection of questionnaires from respondents. The respondents in this research consisted of 50 participants, including students, teachers, and the members of the community. The data obtained from questionnaires were analyzed using multivariate analysis in the XLSTAT application, which calculations conducted through the Principal Component Analysis (PCA) and Factor Analysis (FA) methods. The results of the PCA indicated factors (F) with Eigenvalues of 8.668 for F1, 0.732 for F2, 0.371 for F3, and 0.0299 for F4 which corresponded to variability values of 86.6% for F1, 7.320% for F2, 3.709% for F3, and 2.295% for F4. In contrast, the Factor Analysis (FA) produced variability values (%) of 45.284 for D1, 20.101 for D2, with cumulative percentages (%) of 45.284 for D1 and 65.385 for D2. A cumulative percentage of 65% was deemed adequate to represent the variables reflecting the respondents’ emotional responses.